The Neurophysiological Impact of Experimentally-Induced Pain on Direct Muscle Spindle Afferent Response: A Scoping Review - Lima, Carla R.; Sahu, Pradeep K.; Martins, Daniel F.; Reed, William R. (Frontiers in Cellular Neuroscience, 2021)
Background: Musculoskeletal pain disorders are among the leading causes of years lived with disability worldwide representing a significant burden to society. Studies investigating a “nociceptive-fusimotor” relationship using experimentally-induced pain/noxious stimuli and muscle spindle afferent (MSA) response have been published over several decades. The purpose of this scoping review was to systematically identify and summarize research findings related to the impact of experimentally-induced pain or noxious stimulation on direct MSA discharge/response. Methods: PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane and Embase were searched from database inception to August 2020. Eligible studies were: (a) published in English; (b) clinical or pre-clinical studies; (c) original data studies; (d) included the investigation of MSA response to experimentally-induced pain or noxious stimulation; (e) included quantification of at least one direct physiological measure associated with MSA activity/response. Two-phase screening procedures were conducted by a pair of independent reviewers and data extracted from eligible studies. Results: The literature search resulted in 195 articles of which 23 met inclusion criteria. Six studies (26%) were classified as clinical and 17 (74%) as pre-clinical. Two clinical studies investigated the effects of sacral dermatome pin-pricking on MSA response, while the remaining 4 studies investigated the effects of tonic muscle and/or skin pain induced by injection/infusion of hypertonic saline into the tibialis anterior muscle or subdermal tissues. In pre-clinical studies, muscle pain was induced by injection of noxious substances or the surgical removal of the meniscus at the knee joint. Conclusion: Clinical studies in awake humans reported that experimentally-induced pain did not affect, or else slightly decreased MSA spontaneous discharge and/or response during weak dorsiflexor muscle contraction, thus failing to support an excitatory nociceptive-fusimotor relationship. However, a majority of pre-clinical studies indicated that ipsilateral and contralateral muscle injection of noxious substances altered MSA resting discharge and/or response to stretch predominately through static fusimotor reflex mechanisms. Methodological differences (use of anesthesia, stretch methodology, etc.) may ultimately be responsible for the discrepancies between clinical and pre-clinical findings. Additional investigative efforts are needed to reconcile these discrepancies and to clearly establish or refute the existence of nociceptive-fusimotor relationship in muscular pain.